Identification of a Missense Mutation in the FLNC Gene from a Chinese Family with Restrictive Cardiomyopathy - Dong J; Zhang W; Chen Q; Zha L (Journal of Multidisciplinary Healthcare)
Jiangtao Dong,1– 4,* Wenjuan Zhang,5,* Qianwen Chen,1– 3,6 Lingfeng Zha1– 3 1Department of Cardiology, Union Hospital, Tongji Medical College, Huazhong University of Science and Technology, Wuhan, 430022, People’s Republic of China; 2Hubei Key Laboratory of Biological Targeted Therapy, Union Hospital, Tongji Medical College, Huazhong University of Science and Technology, Wuhan, 430022, People’s Republic of China; 3Hubei Provincial Engineering Research Center of Immunological Diagnosis and Therapy for Cardiovascular Diseases, Union Hospital, Tongji Medical College, Huazhong University of Science and Technology, Wuhan, 430022, People’s Republic of China; 4Department of Cardiovascular Surgery, Union Hospital, Tongji Medical College, Huazhong University of Science and Technology, Wuhan, 430022, People’s Republic of China; 5Department of Geriatrics, The Central Hospital of Wuhan, Tongji Medical College, Huazhong University of Science and Technology, Wuhan, 430022, People’s Republic of China; 6Department of Pediatric Cardiology, Maternal and Child Health Hospital of Hubei Province, Tongji Medical College, Huazhong University of Science and Technology, Wuhan, 430070, People’s Republic of China*These authors contributed equally to this workCorrespondence: Lingfeng Zha, Department of Cardiology, Union Hospital, Tongji Medical College, Huazhong University of Science and Technology, 1277 Jiefang Avenue, Wuhan, 430022, People’s Republic of China, Tel +86-15827177185, Email zhalf@hust.edu.cnObjective: Restrictive cardiomyopathy (RCM) is a heterogenous cardiomyopathy with various causes, and genetic variants take an important part of the pathogenesis. Whole-exome sequencing (WES) is effective to discover genes that cause genetic diseases. By using WES, we attempted to identify the genetic cause of an RCM family and clarify the clinical diagnosis of the patient and then provide a personalized treatment plan.Materials and Methods: Blood samples were obtained from the proband and his healthy parents. WES and Sanger sequencing were performed to identify the possible pathogenic gene. Co-segregation analysis was conducted for candidate variants, and the allele frequency was checked in databases including Ensembl, Exome Aggregation Consortium (ExAC) and Human Gene Mutation Database (HGMD). Furthermore, the potential effect of variant was predicted using various-free software such as SIFT, Polyphen-2 and Mutation Taster and the conservation was tested using multiple sequence alignments by ClustalX.Results: The proband was a 20 years old boy with severe heart failure symptoms including dyspnea, massive ascites, edema of both lower limbs and chest congestion. Echocardiography showed significant biatrial enlargement, normal left ventricular wall thickness and preserved systolic function of both ventricles. A missense mutation in FLNC (c.6451G>A, p.G2151S), encoded filamin-C was detected in proband by WES and Sanger sequencing, while it was not be found in his parents, we supposed that the FLNC mutation (c.6451G>A, p.G2151S) may be a de-novo mutation. Through multiple functional predictions, we found that it is a deleterious mutation and the mutation in filamin-C could alter its structure and normal function, contributing to RCM.Conclusion: Here, an FLNC missense mutation (c.6451G>A, p.G2151S) known to be pathogenic in hypertrophic cardiomyopathy, was found to be associated with RCM, indicating the genetic overlap among cardiomyopathies. This study provides insights into Phenotype-Genotype Correlations of RCM in patients with FLNC mutations.Keywords: restrictive cardiomyopathy, whole-exome sequencing, filamin-C, FLNC